FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA FRAUD PADA DINAS PENGELOLAAN KEKAYAAN DAN KEUANGAN DAERAH - Taufik Edrin Saputra; Andreas '; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Fraud is a intentionally faulth which could harming many people in goverment sector, fraud is harming for public. This research is aimed to anylyze the perception of employees in goverment agencies about factors that impact fraud. Data in this research were collected using a survey method with help of research instruments such as questionnaires were distibuted to 81 employees by respondent goverment agencies working in finance and wealth management agency. Data in this research will be analyzed using multiple linear regression using SPSS ver.20.0. To test the validity and reability of research instrument used pearson correlation and cronsbach alpha. There are several findings in this research, first all instruments used in this research was reliabel and valid. Second, distribution of respondens was normal. Third, the result of the research showed that there is an effect betwen leadership style with fraud with significant 0.039, there is an between effectivenesess of internal contro with fraud with significant 0.000, there is an effect between approprriateness compensation with fraud with significant 0.006, there is an effect between organization commitment with fraud with significant 0.003, there is an effect between organization ethical culture with fraud with significant 0.000.Keywords : leadership, fraud, organizational commitment, appropriateness Compensation and effectiveness of internal control